Frequency and Reasons for Return to the Primary Acute Care Service among Lymphoma Patients Undergoing Inpatient Rehabilitation - Fu, Jack B. (2013)
OBJECTIVE: To assess the frequency and risk factors for return to the primary acute care service among lymphoma patients undergoing inpatient rehabilitation. DESIGN: Retrospective study. SETTING: Tertiary referral-based cancer center. PATIENTS: All patients with a history of lymphoma admitted to inpatient rehabilitation between October 1, 2003 and January 30, 2013. MAIN OUTCOME MEASURES: Items analyzed from patient records included return to the primary acute care service with demographic information, lymphoma characteristics, medications, hospital admission characteristics, and laboratory values. RESULTS: 143 unique patient admissions were analyzed. 54/143 (38%) of lymphoma inpatient rehabilitation admissions returned to the primary acute care service. However, 16/54 (30%) returned due to needing additional chemotherapy. Excluding patients who returned to the primary acute care service for chemotherapy, statistically significant or approaching statistically significant factors (p<.10) associated with return to the primary acute care service included a creatinine greater than or equal to 1.3 milligrams/deciliter (mg/dL) (p=0.0002), male sex (p=0.001), history of hematopoietic stem cell transplant (p=0.0355), and presence of intravenous antifungal agent (p=0.0717). Of those transferred back to the primary acute care service; 13/38 (34%) discharged directly home, 10/38 (26%) died in the hospital, 7/38 (18%) transferred to a subacute rehabilitation facility, and 4/38 (11%) transferred to inpatient rehabilitation. CONCLUSIONS: Chemotherapy was the most common reason for return to the primary acute care service. When excluding patients who returned for chemotherapy, lymphoma patients who are male, who have had a hematopoietic stem cell transplant, and have a creatinine greater than or equal to 1.3 mg/dL demonstrated increased risk for return to the primary acute care service.